On the Validity of Some Arguments for Choral Performance of Stesichorus’ Poems - Brykova, Natalia (Hyperboreus, 2022)
The paper examines three arguments by E. Cingano (Cingano 1993) in favour of the hypothesis that the works of Stesichorus were intended for choral performance. First, the words φιλόμολπε, µολπάς and ἀρχεσίμολπον are analyzed (Stes. fr. 90; 271; 278 F.). According to Cingano, the words with the root μελπ-/μολπ- refer to a choral song accompanied by a dance. Hence, the use of words with this stem by Stesichorus demonstrates the participation of the chorus in the performance of his poems. However, there are testimonies that confirm that μέλπομαι and μολπή can also refer to a soloist singing without being accompanied by dance. Second, the fragment from Stesichorus’ Oresteia (fr. 172 F.) is examined. According to Cingano, it contains indications of a choral performance. However, the participle ἐξευρόντα<ς>, though the emendation of the singular form into the plural must be accepted, does not denote a choral performance of the Oresteia. The hapax δαμώματα describes the public performance of the poem, but it does not mean that the chorus was involved in the performance, since a soloist citharode could also sing for people at feasts and in contests. Neither is the verb ὑμνεῖν an unambiguous indication of choral singing (cf. Hes. Th. 33). Third, the passage of Timaeus (FGrHist 566 F 32. 6–13) is parsed. It refers to “the paeans of Stesichorus, Phrynichus and Pindarus” which several people sung after dinner. However, the text is not sound, and it cannot be excluded that the paeans were attributed only to the last of the mentioned poets, Pindarus. Furthermore, singing after dinner can hardly be considered as an authentic performance of the poems by Stesichorus. Moreover, the participants of a symposium could sing one after another instead of as a chorus. Finally, even if Stesichorus’ paeans did exist, it is difficult to identify them with the preserved fragments of his poems. Thus, none of the observations made by Cingano prove that the extant fragments of Stesichorus’ songs belong to the choral lyrics.